Analisis Majas Perbandingan Dalm Kumpulan Puisi Debu Waktu Dalam Kajian Stilistika - Siti Afifah; Tuti Herawati; Dailami Dailami; Tarida Ilham (Universitas Asahan, 2023)
The purpose of this study is to find out the comparative of figurative language in the collection of poetry Debu Waktu by Tarida Ilham Manurung in a stylistic study. This research belongs to a qualitative method, descriptive type, with the object is a collection of Debu Waktu poetry, written by Tarida Ilham Manurung. The data source used is the primary data source, namely the collection of Debu Waktu poetry, written by Tarida Ilham Manurung, which is published by Azka Gemilang on October 2021 and the secondary data source, namely in the form of references from books, journals, theses, the internet, and etc. Data collection techniques are using reading and note techniques. The results of the discussion of Debu Waktu poetry, written by Tarida Ilham Manurung, there are seven types of comparative figures of languages6, namely 26 figures of personification, 4 of depersonification, 9 of hyperbole, 3 of metaphors, and 2 of dysphemism, with 1 of symbolic figures, and 1 of litotes, with the totaling 2 ( two).